2018
DOI: 10.1108/jmlc-10-2017-0059
|View full text |Cite
|
Sign up to set email alerts
|

Financial crime, corruption and tax evasion: a cross-country investigation

Abstract: Purpose This paper aims to examine the relationship between the financial crime and tax evasion and tests whether corruption moderates such a relationship. Design/methodology/approach Tax evasion measure is based on Schneider et al. (2010). Financial crime is collected from Basel anti-money laundering (AML) report. Findings Using a sample of 120 countries, the authors find that the level of financial crime is positively associated with tax evasion. When testing for the moderating effect of corruption, they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 9 publications
4
31
1
Order By: Relevance
“…Corruption may harm the level of transparency in one country (Amara and Khlif, 2018). Corruption may decrease the capability of any country to enforce laws and penalize individuals that commit financial crimes (Amara and Khlif, 2018).…”
Section: Moderating Effect Of the Strength Of Auditing And Reporting Standards On The Association Between Corruption And Money Launderingmentioning
confidence: 99%
See 2 more Smart Citations
“…Corruption may harm the level of transparency in one country (Amara and Khlif, 2018). Corruption may decrease the capability of any country to enforce laws and penalize individuals that commit financial crimes (Amara and Khlif, 2018).…”
Section: Moderating Effect Of the Strength Of Auditing And Reporting Standards On The Association Between Corruption And Money Launderingmentioning
confidence: 99%
“…Corruption may harm the level of transparency in one country (Amara and Khlif, 2018). Corruption may decrease the capability of any country to enforce laws and penalize individuals that commit financial crimes (Amara and Khlif, 2018). Reganati and Oliva (2018, p. 405) suggest that "corruption and money laundering are two intrinsically linked types of crime".…”
Section: Moderating Effect Of the Strength Of Auditing And Reporting Standards On The Association Between Corruption And Money Launderingmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement of tax evasion using shadow economy has been widely used by several studies (Amara and Khlif, 2018;Cebula, 1997;Khlif and Guidara, 2018). According to Smith (1994), shadow economy is the production of goods and services both legal and illegal that are missed from the calculation of Gross Domestic Product (GDP).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…That makes companies to have no legal rights, so corruption can mitigate these risks by bribing corrupted officials to act as law enforcers (Goel and Saunoris, 2014). In addition, Amara and Khlif (2018) added that high levels of corruption could form a favorable environment for the development of financial crime in the form of illegal economic activities which would result in higher tax evasion. Picur and Riahi-Belkaoui (2006) conducted empirical research from 30 developed and developing countries, the results showed that the highest tax compliance in a country was marked by high control of corruption and low bureaucracy.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%